Society Concern on Fire on Forests and Land Checked on Ciberspace (Research, Society and Development, 2019)
Wildfires on land and forests that occur mainly in regions of the interior of Brazil. These destroy the surroundings and can affect the lives of people in the vicinity. The amount of these offenses has increased annually. It is interesting to see the interest of society in relation to the issue. The purpose of this paper is to describe the perception of Brazilians in cyberspace in relation to burning. A netnographic research of quantitative nature and qualitative bias is carried out in which the number of websites approaching the theme for several periods is observed. It seems that there is an increase in the amount of information and therefore interest in the subject.